PENGARUH JENIS ROLE STRESS PADA KINERJA AUDITOR DENGAN BURNOUT SEBAGAI INTERVENING PADA KAP DI BALI - Trisnawati, Meita; Ramantha, I Wayan; Sari, Maria M. Ratna (Buletin Studi Ekonomi, 2017)
Auditor is profession with high level of stress that lead to burnout. The intention of this study is to obtain observed information of the effect of role conflict, role ambiguity and role overload on auditor performance. To obtain empirical evidence of the effect of role conflict, role ambiguity and role overload to burnout. To achieve observed information of the impact of burnout on auditor performance. To persuade the capability of burnout in mediating the effect of role conflict, role ambiguity and role overload on auditor performance. The population of this research is all public accounting offices in Bali Province. The sample is chosen by purposive sampling method with criteria of auditors with working experience at public accounting office at least one year and auditors who have done minimum one audit assignment. Data are analyzed using path analysis. The test outcome show that role conflict and role ambiguity have negative impact to auditor performance. Role conflict, role ambiguity and role overload have positive effect on burnout. Burnout is able to fully mediate the negative effect of role conflict, role ambiguity and role overload on auditor performance. Keywords: auditor performance, role conflict, role ambiguity, role overload and burnout